Intestine Explants in Organ Culture: A Tool to Broaden the Regenerative Studies in Echinoderms - Samir A. Bello; José E. García-Arrarás (Journal of Marine Science and Engineering, 2022)
The cellular events underlying intestine regrowth in the sea cucumber Holothuria glaberrima have been described by our group. Currently, the molecular and signaling mechanisms involved in this process are being explored. One of the limitations to our investigations has been the absence of suitable cell culture methodologies, required to advance the regeneration studies. An in vitro system, where regenerating intestine explants can be studied in organ culture, was established previously by our group. However, a detailed description of the histological properties of the cultured gut explants was lacking. Here, we used immunocytochemical techniques to study the potential effects of the culture conditions on the histological characteristics of explants, comparing them to the features observed during gut regeneration in our model in vivo. Additionally, the explant outgrowths were morphologically described by phase-contrast microscopy and SEM. Remarkably, intestine explants retain most of their original histoarchitecture for up to 10 days, with few changes as culture time increases. The most evident effects of the culture conditions on explants over culture time were the reduction in the proliferative rate, the loss of the polarity in the localization of proliferating cells, and the appearance of a subpopulation of putative spherulocytes. Finally, cells that migrated from the gut explants could form net-like monolayers, firmly attached to the culture substrate. Overall, regenerating explants in organ culture represent a powerful tool to perform short-term studies of processes associated with gut regeneration in H. glaberrima under controlled conditions.